(untitled) (Journal of Medical Sciences, 2024)
Introduction: the uterus is a muscular organ with a thick wall located between the rectum and urinary bladder. uterine fibroids are most common growths develop either in or around the uterus. Also, they are considered as common gynecological tumors in women at reproductive age. However, its symptoms were affecting the Women’s quality of life. Aims: The main aim of this study is to investigate the anatomical locations of uterine fibroids in Libyan women at Benghazi Medical Center (BMC) between Jan. 1st 2023 to Fab. 1st 2024. Methods: The current study included 200 patients of uterine fibroids of Libyan women in Benghazi confirmed after investigated at the BMC clinically and ultrasonographically. Result: Most of our population were symptomatic fibroids representing 73.8%. The highest frequency was observed in the 36 – 40 years age group. Intramural (34.9%), Submucosal-intramural -intramural (15.1%), and intramural-sub-serosal (21.4%) were the three most frequent anatomical locations of uterine fibroids. Conclusion: The present study found that the individual intramural uterine fibroids were the commonest type which produce menorrhagia as a common clinical presentation.